2009
DOI: 10.1177/0269215508095362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic or aerobic and resistance training on cardiorespiratory and skeletal muscle function in heart failure: a randomized controlled pilot trial

Abstract: Both aerobic and combined aerobic and resistance training are effective interventions to improve Vo(2peak) in compliant heart failure patients. Combined training may be more effective in improving muscle strength and endurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 25 publications
1
56
0
5
Order By: Relevance
“…Mandic and colleagues (2009) 28 demonstrated that combined aerobic and resistance-supervised training significantly improved strength and muscular endurance, by one-repetition maximum test, compared with aerobic training or usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Mandic and colleagues (2009) 28 demonstrated that combined aerobic and resistance-supervised training significantly improved strength and muscular endurance, by one-repetition maximum test, compared with aerobic training or usual care.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that muscle strength improved after a combined aerobic and resistance exercise was similar to that in previous studies. 20,75,76 …”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 displays the relationship between minutes per week of aerobic-type exercise training and change in exercise capacity for 16 randomized trials reported in the meta-analysis conducted by Smart and Marwick 11 in 2004, along with the results from 15 additional trials of similar design. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Regarding Figure 1, note that an increase of at least 1 mL˙kg Ϫ1˙m in Ϫ1 was observed in 28 of the 31 studies. The absence of a significant dose-response relationship across these studies is likely due, in part, to differences in both trial duration (ie, 4 weeks to 14 months) and exercise training intensity.…”
Section: Hf-actionmentioning
confidence: 99%